(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper analyzes Jeanette Winterson’s Sexing the Cherry and The Stone Gods as pivotal quantum narratives that upset the old metaphysic and epistemology in their insistence on the collapse of the natural and artistic in the tradition of linear time, retaining openness in places which are potential, imaginative and creative flesh in rethinking traditional notions of time, identity, and love. Key to this analysis is the non-linearity of temporality, the fluid and changeable nature of gender identity, and love as a transcendental force moving beyond spatio-temporal features. Grounded in theoretical constructions within quantum physics and feminist philosophy, specifically the theories of agential realism (Barad, 1996) and cyborg theory (Haraway, 1985), the analysis shows how Winterson’s narratives use the concept of intra-action to dissolve the borders between self and other, past and present, and in turn, challenging binaries. The significance of the study is the methodology of the research that connects literary study with posthumanist theory to investigate how Winterson’s quantum stories are emancipatory in strategy to encourage rethinking rigidishin to embrace multiplishin, fluidishin and at-the-samishin/style facishin of being. This study demonstrates that Winterson’s innovative narratives not only challenge traditional time and identity paradigms but also locate love and storytelling as transformative agencies that usher in new beginnings and alternate ways of seeing human experience in an interconnected world.